Physics test of water in refill drinking water in Tanjung Morawa Sub-district, Deli Serdang District - Prahesti, Ajeng; Darmirani, Yosi; Suprianto (Medistra Medical Journal (MMJ), 2025)
Introduction: Humans use water to fulfill various daily needs. Each individual's water needs vary from one location to another and at each level of demand. The higher the standard of living in a place, the greater the need for water. Objective:  This study aims to examine the quality of water in several depots in Tanjung Morawa District. Method: The method used in this study is a gravimetric method in which the parameters measured determine the quality of water, namely TDS (Total Dissolved Solid) and TSS (Total Suspended Solid). Then measure the pH using a universal pH indicator, litmus paper and a pH meter. As well as the measurement of taste and turbidity. Result: The results of this study indicated that 8 out of 9 samples of TDS levels had levels higher than the maximum 2010 PERMENKES quality standard, namely 500 mg/L. TSS (Total Suspend Solid) is still lower when compared to the maximum standard content of refill drinking water stipulated by SNI (Indonesian National Standard) for clean water, which is 50 mg/L. The pH level is within normal limits, there is a sweet taste in drinking water and at turbidity levels clear drinking water has particles and is clear without particles.